Construction of Ukranian National Identity by Hidden Curriculum - Shcherbak, Ihor (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2017)
The article analyzes the factors of constructing the national identity in the conditions of modern Ukrainian society. Attention is focused on such of them as education, in particular the hidden curriculum. Considered the theoretical research of the educational system as an institution that significantly influences the formation of social identities. It researches the particularity of the phenomenon of national identity, it's conditionality by the ambiguity of the nation's understanding. Indicators of national identity's substantive content are defined. The analysis results of the discursive construction of the Ukrainian national identity are shown by objectified aspect of hidden curriculum as school books. Identified political and ethnic aspects of national identity, presented in the textbooks reviewed. To determine the influence of identity policies that Implemented by the hidden curriculum, a quantitative analysis of sociological information is carried out, wherewith three groups of national identity values are singled out and their interiorization by pupils.